Pengaruh Pemberian Video Edukasi Perawatan Payudara Terhadap Pengetahuan Ibu Hamil Tm III Dengan Usia Kehamilan 34 -40 Minggu Di Klinik Kartika Jaya Kota Samarinda - Mursidah; Dwi Hartati (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Breast care during pregnancy is essential for the breastfeeding process. Increasing pregnant women's knowledge can be achieved through health education on breast care using video media. Based on research and questionnaire responses before the provision of video media, 19 respondents (63.3%) had low knowledge about breast care at Kartika Jaya Clinic in Samarinda, indicating a lack of awareness among pregnant women regarding breast care. Objective: To determine the effect of educational video media on breast care knowledge among third-trimester pregnant women. Methods: This study employed a pre-experimental design with a "one-group pretest and posttest design" to assess the impact of video education on breast care knowledge among third-trimester pregnant women. The study used a total sampling method with a sample size of 30 respondents. A questionnaire was used as an instrument to measure knowledge about breast care. Results: The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant increase in knowledge, proving that video media is effective in providing health education for third-trimester pregnant women at Kartika Jaya Clinic, Samarinda. Conclusion: Educational videos can enhance knowledge about breast care at Kartika Jaya Clinic, Samarinda. Recommendation: The use of educational video media should be encouraged to make health education more engaging.